2014
DOI: 10.1016/j.bbmt.2014.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Linear Accelerator–Based Intensity-Modulated Total Marrow Irradiation and Myeloablative Fludarabine/Busulfan: A Phase I Study

Abstract: Here we examined the addition of intensity-modulated total marrow irradiation (TMI) delivered using a linear accelerator to a myeloablative chemotherapy conditioning regimen before allogeneic hematopoietic stem cell transplantation (HSCT). In this phase I study, we enrolled 14 patients with high-risk hematologic malignancies who received escalating doses of TMI at 3 Gy (n = 3), 6 Gy (n = 3), 9 Gy (n = 6), and 12 Gy (n = 2) in combination with intravenous (i.v.) fludarabine 160 mg/m(2) and targeted busulfan (ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
38
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 45 publications
1
38
0
3
Order By: Relevance
“…Recently, other investigators have also explored the use of TMI in preparative regimens 2931 . The timing of dose-escalated irradiation relative to chemotherapy seems to be an important consideration as in some studies, dose escalation was feasible and well tolerated, while in others dose-limiting toxicities were striking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, other investigators have also explored the use of TMI in preparative regimens 2931 . The timing of dose-escalated irradiation relative to chemotherapy seems to be an important consideration as in some studies, dose escalation was feasible and well tolerated, while in others dose-limiting toxicities were striking.…”
Section: Discussionmentioning
confidence: 99%
“…While the chemotherapeutic agents were different, the first trial was well tolerated, with dose escalation up to 15Gy, while the second resulted in significant, grade 4 dose limiting toxicities. Similarly, Patel et al used a linac-based TMI method where irradiation and fludarabine were given simultaneously, followed by Busulfan 31 . These investigators found dose limiting toxicities at 12 Gy and concluded that 9 Gy was the MTD.…”
Section: Discussionmentioning
confidence: 99%
“…Although multiple groups have reported posttransplant relapse as a major detriment to survival in a patient with hematologic malignancies, escalation of the conditioning regimen, either through more intense chemotherapy or an increased TBI dose, has typically increased serious or fatal treatment‐related complications . Targeted marrow irradiation as a component in the conditioning regimen is therefore attractive as a means of escalating dose to hematologic tissues while limiting dose to critical structures to an acceptable level, hopefully improving survival .…”
Section: Discussionmentioning
confidence: 99%
“…В данной работе авторы демонстрируют техническую возможность применения Томотерапии для ТОТ и отмечают, что клиническая валидация этого подхода будет представлять несомненный интерес. Недавние исследования убедительно продемонстрировали, что ТОКМ и ТОТ, выполненные на современных классических линейных ускорителях с использованием VMAT, могут обеспечить адекватное покрытие мишени и снижение дозы в органах риска по сравнению со стандартными методиками ТОТ [42][43][44][45][46][47][48][49].…”
unclassified